Balancing Instrumental, Biographic and Social Competencies: Enhancing the Participation of Young Adults in Economic and Social Processes - Danny Wildemeersch; Theo Jansen; Wiltrud Gleseke; Knud Illeris; Susan Weil; Manuela Marninho (Adult Education Research Conference, 2000)
No abstract available.